The pandemic within the pandemic: the surge of neuropsychological disorders in Italian children during the COVID-19 era - Elena Bozzola; Pietro Ferrara; Giulia Spina; Alberto Villani; Marco Roversi; Massimiliano Raponi; Giovanni Corsello; Annamaria Staiano; the Italian Pediatric COVID-19 Board (Italian Journal of Pediatrics, 2022)
Abstract Background Quarantine and isolation measures during COVID-19 pandemic may have caused additional stress and challenged the mental health of the youth. Aim of the study is to investigate the COVID-19 pandemic impact on neuropsychological disorders (NPD) of Italian children and adolescents to provide general pediatric recommendations. Material and methods A retrospective multicenter observational study was planned by the Italian Pediatric Society (SIP) to explore the impact of COVID-19 on the access of children to pediatric Emergency Departments (pED) for the evaluation of neuropsychological symptoms, collecting the classification codes of diagnoses between March 1, 2019 and March 2, 2021. The period study was split into two sub-periods: a pre COVID-19 period (from March 1 2019 to March 1, 2020) and a COVID-19 period (from March 2, 2020 to March 2, 2021). As additional information, data on NPD hospitalizations in any pediatric department of the involved centers were recorded. Results During the study period, a total of 533,318 children were admitted to the pED involved in the study. Despite a 48.2% decline of pED admissions, there was a significant increase (83.1%) in patient admissions for NPD. The most frequent NPD conditions which increased during the COVID-19 pandemic were suicidal ideation (+ 147%), depression (+ 115%), eating disorder (+ 78.4%), and psychosis (+ 17.2%). During the pandemic period, a 39.5% increase in NPD hospitalizations was observed as well. The NPD disorders that mostly required hospitalizations were suicidal ideation (+ 134%), depression (+ 41.4%), eating disorder (+ 31.4%), and drug abuse (+ 26.7%). COVID-19 pandemic had a major impact on children's health, mainly on their NPD development. Neuropsychological assessment should be required at the primary level, in the pediatrician's office, to facilitate early capture of the sign of impairment and provide an adequate treatment. Conclusion SIP underlines the psychological consequences of COVID 19 pandemic on the youngest and recommends an early identification of NPD in the pediatric population to avoid other serious consequences for children's physical and mental health.